Floristic and structural patterns in South Brazilian coastal grasslands - MENEZES, LUCIANA S.; MÜLLER, SANDRA C.; OVERBECK, GERHARD E. (Anais da Academia Brasileira de Ciências, 2015)
ABSTRACT The natural vegetation of Southern Brazil's coastal region includes grasslands formations that are poorly considered in conservation policy, due to the lack of knowledge about these systems. This study reports results from a regional-scale survey of coastal grasslands vegetation along a 536 km gradient on southern Brazil. We sampled 16 sites along the coastal plain with 15 plots (1 m²) per site. All sites were grazed by cattle. We estimated plant species cover, vegetation height, percentage of bare soil, litter and manure, and classified species according to their growth forms. We found 221 species, 14 of them exotic and two threatened. The prostate grasses: Axonopus aff.affinis, Paspalum notatum and P. pumilumwere among the most important species. Prostrate graminoids species represented the most important vegetation cover, followed by cespitose grasses. Vegetation height, bare soil, litter and manure were similar among all areas, highlighting the homogeneity of sampling sites due to similar management. In comparison to other grasslands formations in Southern Brazil, the coastal grasslands presented rather low species richness. The presence of high values for bare soil at all sampling sites indicates the need to discuss management practices in the region, especially with regard to the intensity of livestock grazing. RESUMO A vegetação natural da região costeira sul brasileira inclui formações campestres que são pouco consideradas nas políticas de conservação, devido a falta de conhecimento sobre estes ecossistemas. Esse estudo reporta resultados de um levantamento em escala regional da vegetação campestre costeira ao longo de um gradiente de 536 km no sul do Brasil. Amostramos 16 áreas ao longo da planície costeira com 15 parcelas (1m²) por área. Todas as áreas eram pastejadas por gado. Estimamos cobertura de espécies de plantas, altura da vegetação, porcentagem de solo descoberto, mantilho e esterco, e classificamos as espécies de acordo com suas formas de crescimento. Encontramos 221 espécies, 14 dessas exóticas e duas ameaçadas. As gramas prostradas: Axonopus aff.affinis, Paspalum notatum e P. pumilumestavam entre as espécies mais importantes. Espécies de gramíneas prostradas representaram a cobertura vegetal mais importante, seguidas por gramas cespitosas. Altura da vegetação, solo descoberto, mantilho e esterco foram similares entre todas as áreas, destacando a homogeneidade das áreas amostrais devido ao manejo similar. Em comparação com outras formações campestres no sul do Brasil, os campos costeiros apresentaram riqueza de espécies bastante baixa. A presença de altos valores de solo descoberto em todas as áreas amostrais indica a necessidade de discutir as práticas de manejo na região, especialmente no que diz respeito a intensidade de pastejo do gado.